A posição das organizações hospitalares em relação à acreditação - Marques, Liane Freitas (2006)
Focusing on the Brazilian Accreditation Program, the main objective of this study is to analyze the position on accreditation of hospital services organizations. It intends to map the hospital management practices and understand the way those organizations perceive the benefits and difficulties to implement this program. The study encompasses hospitals from the Hospital Management Learning and Innovation Network Bahia State InovarH, and other hospitals outside this network, all located in Bahia State. This is, at the same time, an exploratory and descriptive research. It is exploratory because the hospitals accreditation position is a theme that has not been studied yet. It is a descriptive research because it aims to describe the Bahia state hospital services organizations positions about accreditation. Regarding research means, it is a filed research. The study characterizes the hospital organizations practices with focus on the way they perceive the accreditation process, using as reference the ONA (Organização Nacional de Acreditação) Brazilian accreditation program. The research results analysis indicates that majority of the hospital organizations researched knows the program and is interested in hospital accreditation. The study also found that organizations in general have management practices that are close to the Brazilian Accreditation Manual requisites, but they have difficulties in engaging to a program implementation, as consequence of a series of factors. The work concluded that relevant hospitals in the market comprising Salvador, Lauro de Freitas and Itaparica, public and private ones, have a favorable position to accreditation, but they need support to the implementation process.